A Building Material from the Upper Jurassic Period into the Canarian Architectural Heritage: The Durability of the Heartwood of Pinus Canariensis. Issue 1 (2nd January 2022) - González Díaz, Eduardo; García, Marcos Frías; Asensio, Isaac Alonso; González, Enrique; Alonso López, José Manuel
ABSTRACT: The durability of building materials is a fundamental issue addressed by many researchers who seek to improve working life by obtaining durable and more sustainable materials. In the Canary Islands, there are traditional buildings with carpentry elements that remain unchanged, without any apparent degradation. Specifically, the wood used in Canarian heritage comes from the resinous heartwood of Pinus canariensis . Most of these buildings were built between the sixteenth and nineteenth centuries, and their architectural relevance has been decisive in declaring the city of La Laguna a World Heritage Site by UNESCO. The objective of this research is to identify the carpentry elements made with the heartwood of Pinus canariensis within the Canarian architectural heritage and to evaluate its durability. The results show that the loss of mass for the heartwood of Pinus canariensis after the incubation of the fungus was less than 1% in all cases. However, other conifers show a considerable loss of mass, between 25% and 38%.